Percutaneous endoscopic gastrostomy for nutritional palliation of upper esophageal cancer unsuitable for esophageal stenting - Grilo, Ana (2012)
"Context - Esophageal cancer is often diagnosed at an advanced stage and has a poor prognosis. Most patients with advanced esophageal cancer have significant dysphagia that contributes to weight loss and malnutrition. Esophageal stenting is a widespread palliation approach, but unsuitable for cancers near the upper esophageal sphincter, were stents are poorly tolerated. Generally, guidelines do not support endoscopic gastrostomy in this clinical setting, but it may be the best option for nutritional support. Objective - Retrospective evaluation of patients with dysphagia caused advanced esophageal cancer, no expectation of resuming oral intake and with percutaneous endoscopic gastrostomy for comfort palliative nutrition. Method - We selected adult patients with unresecable esophageal cancer histological confirmed, in whom stenting was impossible due to proximal location, and chemotherapy or radiotherapy were palliative, using gastrostomy for enteral nutrition. Clinical and nutritional data were evaluated, including success of gastrostomy, procedure complications and survival after percutaneous endoscopic gastrostomy, and evolution of body mass index, albumin, transferrin and cholesterol. Results - Seventeen males with stage III or IV squamous cell carcinoma fulfilled the inclusion criteria. Mean age was 60.9 years. Most of the patients had toxic habits. All underwent palliative chemotherapy or radiotherapy. Gastrostomy was successfully performed in all, but nine required prior dilatation. Most had the gastrostomy within 2 months after diagnosis. There was a buried bumper syndrome treated with tube replacement and four minor complications. There were no cases of implantation metastases or procedure related mortality. Two patients were lost and 12 died. Mean survival of deceased patients was 5.9 months. Three patients are alive 6, 14 and 17 months after the gastrostomy procedure, still increasing the mean survival. Mean body mass index and laboratory parameters were roughly stable 1 and 3 months after the gastrostomy procedure. Conclusions - In patients with advanced upper esophageal cancer where only palliative treatment is possible, nutritional support is easily achieved with percutaneous endoscopic gastrostomy, allowing patients to be at homes, surviving a significant period of time. Percutaneous endoscopic gastrostomy feeding should be considered as standard definitive nutritional palliation in patients with upper esophageal cancer, unsuitable for esophageal stenting."